(untitled) (Journal of Universal Science Research, 2023)
In this article Zahiriddin Muhammad Babur’s greatest work The main topics covered in the work "Boburnoma" are explained from a scientific, historical and educational point of view. The work "Boburnoma" by Zahiriddin Muhammad Babur is noteworthy as a historical literary source because it contains many historical figures, people of literature and art, religious leaders, There is information about branches and princes, beks, amirs and Umars.